Practical considerations for the use of sodium–glucose co-transporter type 2 inhibitors in treating hyperglycemia in type 2 diabetes. (2nd June 2016) - Lam, Karen S.L.; Chow, Chun Chung; Tan, Kathryn C.B.; Ma, Ronald C.W.; Kong, Alice P.S.; Tong, Peter C.Y.; Tsang, Man Wo; Chan, Tak Mao; Tang, Sydney C.W.; Lee, Ka Kui; So, Wing Yee; Tomlinson, Brian
Abstract: Sodium–glucose co-transporter type 2 (SGLT2) inhibitors are a new class of oral anti-diabetic agents with a unique, insulin-independent mode of action. In patients with diabetes who have adequate renal function, SGLT2 inhibitors reduce hyperglycemia by blocking renal glucose reabsorption and increasing urinary glucose excretion. These agents are indicated for the treatment of hyperglycemia in type 2 diabetes mellitus (T2DM), as an adjunct to diet and exercise. In terms of efficacy, they are comparable to most other oral agents, and carry a low risk of hypoglycemia unless combined with sulfonylureas or insulin. They may be used in combination regimens with metformin, sulfonylureas, or insulin. Beyond glucose lowering, SGLT2 inhibitors are associated with modest weight loss and mild anti-hypertensive effects. Emerging cardiovascular and renal outcomes data suggest other potentially beneficial non-glycemic effects, although these findings await confirmation from further studies. The main adverse effects are increased risk of volume depletion and of genitourinary infections, although these can be managed with standard interventions. Rare cases of euglycemic ketoacidosis have been reported in a subset of patients treated with these agents, an issue currently under investigation. SGLT2 inhibitors represent a promising alternative treatment option for T2DM patients in whom the effectiveness of oral anti-hyperglycemic therapy is limited by the risk of hypoglycemia, weight gain, or other adverse effects. Safety and efficacy (up to 4 years) have been demonstrated in a range of T2DM patient populations, although more studies will be needed to determine whether treatment with SGLT2 inhibitors improves patient-important outcomes in the longer term.